Sustainability of Education Process in Higher Education - Rina Karlina; Mayla Khoiriyah (AKRUAL: JURNAL AKUNTANSI, 2021)
The purpose of this study is to analyzed tensions faced by higher education in integrating sustainability into their curriculum, practices and policies during COVID-19 outbreak especially in accounting education. As we know, higher education has an important role in implementing economic, social, and environmental dimensions simultanously. During this pandemic, higher education gets greater tensions in integrating sustainability. This research used qualitative descriptive approach and single case study with several unit of analysis. This research begins with a study of sustainability integration that has been internalized in institutions, analyzing tensions faced by higher education and strategies to mitigate these tensions. We used Riau University and Polythecnic of State Finance STAN as our samples. We found that sustainability integration through curriculum, practices and policies in higher education is not fully implemented. Furthermore, while implementing sustainability higher education faces some tensions at level, change and context dimensions according to framework developed by Hahn et al, (2014). During this COVID-19 pandemic, Higher Education faces greater tensions to integrate sustainability into their curriculum, practices and policies. To mitigate those tensions, they can utilize acceptance and resolution strategies according to their respective needs and consequences